The roaming course: fostering intergroup relationships among Arab and Jewish students in physical education teacher education - Hellerstein, Devora; Sindiani, Mahmood (Frontiers in Political Science, 2025)
PurposeThis study examined a structured intervention designed to enhance intercultural competence and intergroup relations among Arab and Jewish students in a physical education teacher education (PETE) program in Israel.MethodThe 12-week ‘Roaming Course’ included 41 students (14 Arab, 27 Jewish), four study tours in mixed Arab-Jewish cities, and four on-campus sessions. Co-taught by an Arab and a Jewish instructor, the course integrated theoretical instruction, intercultural dialogue, and sport-based activities, drawing on the Contact Hypothesis, the Multi-Dimensional Model of Intercultural Communicative Competence (ICC), and the Sport for Development and Peace (SDP) framework. Qualitative data were collected from students’ reflective journals.ResultsFindings showed that structured intergroup contact in the PETE framework fostered trust, reduced prejudice, and enhanced intercultural awareness, empathy, and professional identity.Discussion and conclusionThe study highlights sport’s role in bridging divides and presents a pedagogical model for higher education institutions promoting intercultural competence in diverse societies.